2012
DOI: 10.1038/nrc3380
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic cell death and DAMPs in cancer therapy

Abstract: Although it was thought that apoptotic cells, when rapidly phagocytosed, underwent a silent death that did not trigger an immune response, in recent years a new concept of immunogenic cell death (ICD) has emerged. The immunogenic characteristics of ICD are mainly mediated by damage-associated molecular patterns (DAMPs), which include surface-exposed calreticulin (CRT), secreted ATP and released high mobility group protein B1 (HMGB1). Most DAMPs can be recognized by pattern recognition receptors (PRRs). In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

15
2,121
1
19

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,357 publications
(2,156 citation statements)
references
References 199 publications
15
2,121
1
19
Order By: Relevance
“…We found that all AC-NP formulations, with the exception of mPEG AC-NPs, successfully captured neoantigens 24 (Figure 2c, Supplementary Table 1). Notably, AC-NPs also captured a number of damage associated molecular pattern proteins (DAMPs), a broad class of pro-inflammatory molecules that have been shown to potentiate immune response 27 . Notably, we found that our AC-NPs were capable of capturing histone proteins and alarmins (including HMGB1), both of which have been shown to enhance anti-tumor immune responses (Supplementary Table 1) 27 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We found that all AC-NP formulations, with the exception of mPEG AC-NPs, successfully captured neoantigens 24 (Figure 2c, Supplementary Table 1). Notably, AC-NPs also captured a number of damage associated molecular pattern proteins (DAMPs), a broad class of pro-inflammatory molecules that have been shown to potentiate immune response 27 . Notably, we found that our AC-NPs were capable of capturing histone proteins and alarmins (including HMGB1), both of which have been shown to enhance anti-tumor immune responses (Supplementary Table 1) 27 .…”
mentioning
confidence: 99%
“…Notably, AC-NPs also captured a number of damage associated molecular pattern proteins (DAMPs), a broad class of pro-inflammatory molecules that have been shown to potentiate immune response 27 . Notably, we found that our AC-NPs were capable of capturing histone proteins and alarmins (including HMGB1), both of which have been shown to enhance anti-tumor immune responses (Supplementary Table 1) 27 . Our data confirm that AC-NPs capture a myriad of TDPAs that are released after radiotherapy.…”
mentioning
confidence: 99%
“…Accumulating evidence now indicates that (at least some) anticancer agents actively stimulate tumor-specific immune responses, which in many cases account for long-term therapeutic successes. [1][2][3][4] Chemotherapy (as well as some forms of radiotherapy) can exert immunostimulatory effects via two alternative, although non-exclusive, mechanisms. First, some cytotoxic anticancer agents, including anthracyclines and oxaliplatin (OXA), are capable of triggering an immunogenic variant of apoptosis known as immunogenic cell death (ICD), 5,6 de facto converting dying cancer cells into a therapeutic vaccine.…”
mentioning
confidence: 99%
“…2,11,12 Thus, the subcutaneous injection of cancer cells that are succumbing to ICD, but not of cells undergoing conventional apoptosis or necrosis, elicits a T-cell-mediated immune response protecting histocompatible mice against a subsequent challenge with tumor cells of the same type. 2,3,13 Of note, most inducers of apoptosis and necrosis fail to trigger ICD. However, a few chemotherapeutics, including anthracyclines, 7,8 OXA, 14 cyclophosphamide, 15 and -to some extent -microtubular inhibitors, 16 as well as cardiac glycosides, [17][18][19] potently do so.…”
mentioning
confidence: 99%
See 1 more Smart Citation